Non archimedean metric induced fuzzy uniform spaces - R. Lowen; A. K. Srivastava; p. Wuyts (International Journal of Mathematics and Mathematical Sciences)
It is shown that the category of non-Archimedean metric spaces with 1-Lipschitz maps can be embedded as a coreflective non-bireflective subcategory in the category of fuzzy uniform spaces. Consequential characterizations of topological and uniform properties are derived.